Thermal stability and flame-retardant characteristic of irradiated LDPE and composites - Sabet, M. (Springer, 2020)
Magnesium hydroxide (MH) and alumina trihydrate (ATH) are extensively consumed as fillers in polyolefins to fabricate naturally responsive cables. Halogen-free wires, and especially cross-linked or thermoplastic elastomers, are further prevalent in worldwide use. The limited oxygen index (LOI), cone calorimeter, smoke density and thermogravimetry (TGA) experiments explain the thermal decomposition, flame-retardant and physical characteristics of samples. Results from studies of TGA, smoke emission and LOI testers showed that the thermal strength and flame-retardant characteristics of the samples containing MH compared with corresponding specimens containing ATH have superior thermal stability. The flame-retardant and heat resistance characteristics of samples were improved due to irradiation and the development of cross-linking bonds in the polymer framework. The results of the smoke density experiment show that adding MH to low-density polyethylene (LDPE) results in the lowest smoke density associated with LDPE and LDPE/ATH compounds. This study proved that the inclusion of MH and irradiation of specimens caused a greater thermal strength and also a superior flame-retardant polymeric product compared with the inclusion of ATH to similar irradiated specimens. These successes are useful and appropriate specifically for cable companies to deliver halogen-free flame-retardant cable materials. Â© 2020, Indian Academy of Sciences.